Ciphering the unnamable through the letter: horror in the poetry of paul celan (2014)
The purpose of this text is to addressthe intersection between horrorand war and its expression in thework of Paul Celan. It examinesone of these manifestations, silence,from the perspective of psychoanalysisand then goes on to discussthe ways in which silence occursin poetry. The conclusion is thatsilence arises due to the impossibilityof ciphering horror by resortingto the letter.